Α-MHC MitoTimer mouse: In vivo mitochondrial turnover model reveals remarkable mitochondrial heterogeneity in the heart. (January 2016) - Stotland, Aleksandr; Gottlieb, Roberta A.
Abstract: In order to maintain an efficient, energy-producing network in the heart, dysfunctional mitochondria are cleared through the mechanism of autophagy, which is closely linked with mitochondrial biogenesis; these, together with fusion and fission comprise a crucial process known as mitochondrial turnover. Until recently, the lack of molecular tools and methods available to researchers has impeded in vivo investigations of turnover. To investigate the process at the level of a single mitochondrion, our laboratory has developed the MitoTimer protein. Timer is a mutant of DsRed fluorescent protein characterized by transition from green fluorescence to a more stable red conformation over 48 h, and its rate of maturation is stable under physiological conditions. We fused the Timer cDNA with the inner mitochondrial membrane signal sequence and placed it under the control of a cardiac-restricted promoter. This construct was used to create the alpha-MHC-MitoTimer mice. Surprisingly, initial analysis of the hearts from these mice demonstrated a high degree of heterogeneity in the ratio of red-to-green fluorescence of MitoTimer in cardiac tissue. Further, scattered solitary mitochondria within cardiomyocytes display a much higher red-to-green fluorescence (red-shifted) relative to other mitochondria in the cell, implying a block in import of newly synthesized MitoTimer likely due to lower membrane potential. These red-shifted mitochondria may represent older, senescent mitochondria. Concurrently, the cardiomyocytes also contain a subpopulation of mitochondria that display a lower red-to-green fluorescence (green-shifted) relative to other mitochondria, indicative of germinal mitochondria that are actively engaged in import of newly-synthesized mito-targeted proteins. These mitochondria can be isolated and sorted from the heart by flow cytometry for further analysis. Initial studies suggest that these mice represent an elegant tool for the investigation of mitochondrial turnover in the heart. Highlights: MitoTimer protein reveals germinal and senescent mitochondria. Mice expressing MitoTimer under a cardiac-specific promoter was generated. MitoTimer expression reveals mitochondrial heterogeneity in cardiomyocytes.